Implementation of Employee Work Ethics (Study on Baitul Maal wa al Tamwil (BMT) Maslahah Cooperation) - Syuhri, Saifuddin (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
Competition from financial institutions such as Baitul Maal Wa Al Tamwil (BMT) cannot be avoided, so employee performance and customer satisfaction are essential in running a business. This research method is descriptive qualitative. The result is that implementing of employee work ethics is influenced by the religious, cultural, socio-political, geographical environment, education and economic structure factors. Meanwhile, the fundamental values as the basis of Islamic work ethics are: monotheism, justice (al Adl), prophethood (a Nubuwah), government (khilafah), results (ma'ad) and carrying out activities based on the principles of siddiq/honesty, tabligh/transparency, Trustworthy/responsible and fathonah/professional as well as avoiding the elements of maysir (gambling), tadlis (fraud), gharar (uncertainty), usury, zulm (persecution), risywah (bribery).